Standardizing the size of pistons in both sexes and comparing the outcome of reverse stapedotomy: our experience - Ghosh, Tushar K.; Dey, Debayan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Stapedotomy is one of the most fascinating surgery in otology. Stapedotomy is an effective surgical procedure for the treatment of otosclerosis which leads to improvement in patients’ quality of life. Methods: Prospective observational study conducted at Ghosh ENT foundation, Kolkata from May 2021 to May 2023 to study the outcome of reverse stapedotomy with microscope and the length of the piston used. Results: Our study comprised of 192 ears operated for otosclerosis, 101 were males and 91 were females. 37 patients were misdiagnosed and prescribed hearing aids without being suggested stapedotomy. The most common associated complaint was tinnitus in both the sexes and only 1 patient complained of vertigo. The most common post op complication was vertigo followed by dysgeusia, Tympanomeatal flap tear was observed in a handful cases and repaired by a tympanoplasty. Our method creates minimal complication and reduces the duration of surgery. We noticed that the average length of the piston required is 4.25 mm in females while for males it is 4.5 mm. only 3 female patients were fitted with 4.5 mm piston. Patients operated by our stapedotomy technique showed that the ABG closure within 10 dB could be achieved in 87% and within 20 dB in 97% of cases without any otologic complications. Conclusions: A good and favourable hearing outcome can be obtained by the combination of experienced hands with minimal surgical trauma and an appropriate surgical technique. This will ultimately lead to less post-operative complications and the need for revision surgery.